Estágios de investimentos e critérios de seleção de startups: a visão dos fundos de venture capital - Rosa, Pamela Alves da (Universidade do Vale do Rio dos Sinos, 2022)
This study seeks to understand the selection criteria for selecting found in the Venture Capital modality in the Brazilian scenario, according to the investment stage of de startups and their evaluation metrics. Taking into account the sectors that most investment through the modality of Venture Capital in Brazil and whether there is a pattern in the evaluation metrics for the startup investment selection process. The Venture Capital investment modality moves millions in the Brazilian market, and has grown steadily remaining without applicable legislation, in comparison with the more developed countries, where this market, in addition to being overheated, is supervised and already has behavioral standards. Based on the data collected from Crunchbase, an investment platform, a semi-structured interview script was made, which was tabulated and analyzed, together with the platform's data. The companies' websites were also visited to corroborate with the data, and afterwards all of them were coded, for the purposes of this study's explanation. At the end of this study, the results show that seed is the early stage that receives the most investments, and that it is evaluated by the multiple evaluation method, compared to companies in the same sector, and that the team and the market are taken into consideration in the evaluation of the companies. As for the sector, most have no preference, as they prefer to diversify their investment portfolios across several sectors. The findings of this study were supported by its literature theories present in this research.
Keywords: Venture capital; Avaliação; Estágio; Startup; Investidor; Valuation; Internship; Investor; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis